THE IMPACT OF NUTRITIONAL STATUS ON THE RISK OF ANEMIA IN PREGNANT WOMEN: A CROSS-SECTIONAL STUDY - Sulpat, Emuliana; Mardhika, Amelia; Fadliyah, Lailatul; Pangestu Mei Tyas, Anestasia; Harianto, Susilo; Marsinta, Frisma Dyah (Universitas Airlangga, 2025)
Introduction: Pregnancy anemia is the cause of the high maternal mortality rate (AKI) in Indonesia. Nutritional status is one of the factors that affect pregnancy anemia. Poor nutritional status in pregnant women increases the risk of developing anemia, which is 6,500 times greater than in mothers with good nutritional status. This study aims to determine the relationship between nutritional status and the incidence of anemia in pregnant women. Methods: The research method used in this study is a quantitative study with a correlational design with a cross-sectional approach. The population in this study is all pregnant women who have their pregnancy checked at the Balerejo Health Center, a many as 50 people. Purposive sampling technique: a sample of 44 people. The independent variable is nutritional status, and the dependent variable is the incidence of anemia. The data was collected using a questionnaire and a LILA ribbon and analyzed using chi-square. Results: The results of the analysis of the chi-square statistical test showed that there was a relationship between nutritional status and the incidence of anemia, with the result of sig-p = 0.000, p< 0.05. Conclusions: It is recommended that pregnant women maintain their body condition by consuming nutritious food to meet the body's needs and avoid a lack of nutritional status and the occurrence of anemia, which can be fatal to death.